Species identification of echinoderms from the North Sea by combining morphology and molecular data. Issue 1 (January 2017) - Laakmann, Silke; Boos, Karin; Knebelsberger, Thomas; Raupach, Michael; Neumann, Hermann
Abstract Background Taxonomic uncertainties in the morphological species identification and taxonomic revisions in individual groups are known for all echinoderm classes. These uncertainties in morphological species identification and discrimination have spawned the application of molecular genetic identification techniques. However, as the fundamental step to allow and ensure future molecular species identification, valid and comprehensive reference library entries comprising morphological and molecular species information together with various metadata are essentially needed. In our study we compare morphological and molecular genetic species identification techniques for representatives of North Sea echinoderm classes, i.e. the Asteroidea, Ophiuroidea, Echinoidea and Holothuroidea. Methods Individuals were sampled during different surveys in different regions of the North Sea, identified to species level based on morphological diagnostic features, and were genetically analysed using a fragment of the mitochondrial cytochrome c oxidase subunit I (COI). Results and Discussion The morphological determination revealed 32 species including one taxon determined only to genus level. In contrast to this, the COI analysis supported 34 monophyletic clades with pronounced differences between the intra- and the inter-specific genetic variability (a barcoding gap of 4.93 %) with highest intra-specific variabilities found in the ophiuroid speciesAmphiura filiformis, A. chiajei andOphiura sarsii . In 94 % of the investigated species, morphological identification and COI sequence clusters were congruent whereas for two asteroid species we found an underestimated diversity. ForAstropecten irregularis, one of the most common starfish species of the North Sea, we found two distinct and possibly depth-related clades, probably sibling species, differing by 11.1–11.9 % sequence divergences (p-distances). For two starfish individuals, morphologically identified asHenricia sanguinolenta, the COI analysis revealed two monophyletic clades, of which one was classified asH. cf.oculata by comparison to published sequences. Conclusions This newly established sequence reference library for the North Sea Echinodermata allows and ensures future molecular species identification for various life-cycle stages including juveniles and meroplanktonic larvae and provides sequences for phylogeographic studies and the detection of sibling as well as cryptic species.